WARNA TENUN DOYO SEBAGAI EXPRESI MASYARAKATNYA (TANJUNG ISUY - KUTAI BARAT) - Mita Purbasari; Anita Rahardja (Universitas Trisakti, 2018)
AbstractTenun Doyo is a type of woven connective made by a live fibers doyo (Curliglia Latifolia). Doyo is a plant kind of a strong pandanus fibrous and growing wild in the Kalimantan’svillage, such as in Tanjung Isuy, Jempang-West Kutai. Weaving is famous not only forusing a basic source of some natural fibers, but also because it tinged with a natural dye.The research focus on experiment composition a variaton of color based on a naturaldye of West Kutai and new motives or patterns based on the surrounding environment.Used qualitative method that based on Research Through Design method. Design as research is known more as Practice Based Research or Action Research, involvingsystimatic research through practical activity. By using the Practice Based Research,the results could be some new things in infomation form to open the insight, possibilityof forms, process, concept and knowledge. The outcome intended to create the colorsvariantions for the pattern or motive, which comes from the nature objects in WestKutai, so the woven doyo’s colors have had more range and finally they have had manyvarioations. Hopefully, the colors’s variations have the meaning that reflecting the valueand culture of West Kutai in general and villages nearby in particular. The existence ofcolors and motives are expected to revitalise the Dayak Benuaq tribe in West Kutai toincrease the willing for weaving in order that the expertise not extinct and sustainableheredity. It can maintain the Tanjung Isuy local indigous and increase the communityproductivity. AbstrakTenun doyo merupakan jenis tenun ikat berbahan serat daun doyo (Curliglia latifolia). Doyo adalah tanaman jenis pandan yang berserat kuat dan tumbuh liar di pedalaman Kalimantan, diantaranya di desa Tanjung Isuy, Jempang, Kutai Barat. Tenun doyo tidak hanya terkenal karena menggunakan bahan dasar serat alami, namun juga karena diwarnai dengan pewarna alami. Penelitian ini fokus pada eksperimen komposisi variasi warna berdasarkan pewarna alami dari Kutai Barat sendiri dan motif baru berdasarkan lingkungan sekitarnya. Menggunakan metode kualitatif di mana metode research through design menjadi dasarnya. Design as research lebih dikenal dengan nama practice based research atau action research, melibatkan riset sistimatis melalui aktivitas praktis. Di manahasilnya dapat merupakan hal-hal baru dalam bentuk informasi untuk membuka wawasan, kemungkinan bentuk-bentuk, proses, konsep, dan pengetahuan. Hasil penelitian ditujukan untuk membuat variasi warna-warna bagi motif yang bersumber dari objek-objek alam di Kutai Barat, sehingga warna tenun doyo